"Who's Better at Math, Boys or Girls?": Changes in Adolescents' Math Gender Stereotypes and Their Motivational Beliefs from Early to Late Adolescence - Christine R. Starr; Yannan Gao; Charlott Rubach; Glona Lee; Nayssan Safavian; Anna-Lena Dicke; Jacquelynne S. Eccles; Sandra D. Simpkins (MDPI AG, 2023)
Though adults tend to endorse the stereotype that boys are better than girls in math, children tend to favor their own gender or be gender egalitarian. When do individuals start endorsing the traditional stereotype that boys are better? Using two longitudinal U.S. datasets that span 1993 to 2011, we examined three questions: (1) What are the developmental changes in adolescents' gender stereotypes about math abilities from early to late adolescence? (2) Do the developmental changes vary based on gender and race/ethnicity? (3) Are adolescents' stereotypes related to their math motivational beliefs? Finally, (4) do these patterns replicate across two datasets that vary in historical time? Adolescents in grades 8/9 and 11 were asked whether girls or boys are better at math (n's = 1186 and 23,340, 49-53% girls, 30-54% White, 13-60% Black, 1-22% Latinx, and 2% to 4% Asian). Early adolescents were more likely to be gender egalitarian or favor their own gender. By late adolescence, adolescents' stereotypes typically shifted towards the traditional stereotype that boys are better. In terms of race/ethnicity, White and Asian adolescents significantly favored boys, whereas Black and Latinx adolescents were more likely to endorse gender egalitarian beliefs. Adolescents' stereotypes were significantly related to their expectancy beliefs, negatively for girls and positively for boys.